2010
DOI: 10.1097/opx.0b013e3181d9515c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impairment Measures and Reading Performance in a Large Age-Related Macular Degeneration Group

Abstract: Optimal prediction of reading speed with clinical parameters appears to be based on the combination of near word acuity and scotoma area, explaining 60% of the variance. Other factors not measured in this study are likely to account for the rest of the prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…5,[10][11][12][13]15 The effects on the reading rate of fixation eccentricity and stability and other features of eye movements, including saccade efficiency, have also been investigated. 11,13,16,18,26 Our study has included several of the abovementioned measures in a large sample of consecutive patients with mild or moderate low vision collected at five low vision service centers in Italy. Because we expected these predictors to be reciprocally correlated and to have at best moderate degrees of independent association with reading performance, including RA and RS, we used SEM to simultaneously explore the network of associations among all variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[10][11][12][13]15 The effects on the reading rate of fixation eccentricity and stability and other features of eye movements, including saccade efficiency, have also been investigated. 11,13,16,18,26 Our study has included several of the abovementioned measures in a large sample of consecutive patients with mild or moderate low vision collected at five low vision service centers in Italy. Because we expected these predictors to be reciprocally correlated and to have at best moderate degrees of independent association with reading performance, including RA and RS, we used SEM to simultaneously explore the network of associations among all variables.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The investigation of the complex associations among clinical predictors of reading ability in low vision patients may be useful to set realistic expectations of low vision rehabilitation and personalize the rehabilitation plan. Previous research has identified several predictors of reading performance in low vision patients, including reading and letter CS, 6,7 the presence of a deep scotoma in the retinal reading area, 5,[8][9][10][11] fixation features (such as eccentricity, usually related to scotoma size), [12][13][14] and fixation stability. [15][16][17] Although microperimetry has increasingly been used in low vision research, 9,10,13,[18][19][20] Micro Perimeter 1 (MP1; Nidek Technologies Inc., Padova, Italy) retinal sensitivity has not been compared with other psychophysical measures as a predictor of reading ability in low vision patients to the best of our knowledge.…”
Section: Methods Standard Measurements Of Reading Ability (Minnesotamentioning
confidence: 99%
“…Many studies followed focusing on different methods of characterizing visual function, and consequently, various methods have been advocated for the evaluation of visual function. For example, scotomas size has been strongly correlated with reading speed, 5 and dVA has been shown to correlate poorly with other visual function parameters. 6 In nAMD and retinal fibrosis caused by nAMD, reading performance decreased more than dVA, 7 and in uveitis-associated cystoid macular edema (uvCME), reading performance was more affected than dVA.…”
mentioning
confidence: 98%
“…Other validated vision function measurements include color vision tests with ''Farnsworth Munsell 100 Hue Test,'' contrast sensitivity, and reading speed. 9 These tests give an overall measure of macular and foveal function but do not allow fine spatially localized testing.…”
mentioning
confidence: 99%